2020
DOI: 10.2217/nnm-2019-0195
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Ability of Human Adipose Stem Cells Exposed to Cobalt Nanoparticles: Outcome of Dissolution

Abstract: Aim:To demonstrate that cobalt nanoparticles doses are safe for use in humans and to understand the consequences of the particulate effects, which may persist inside the cells. Materials & methods: Human adipose stem cells were used. We evaluated cell recovery by viability test, morphology and ultrastructure using electronic and optical microscopy, while gene expression was assessed utilizing real-time PCR. Results: After exposure, most stem cells recovered their normal function. Co 3 O 4 -nanoparticles remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…hASCs were isolated according to Gronthos and Zannettino's protocol modified in our laboratory [27]. Briefly, the stromal vascular fraction (SVF) was obtained by collagenase type II digestion (Sigma Aldrich, Milano, Italy) at 37 • C for 1 h in agitation.…”
Section: Hasc Isolation and Culturementioning
confidence: 99%
“…hASCs were isolated according to Gronthos and Zannettino's protocol modified in our laboratory [27]. Briefly, the stromal vascular fraction (SVF) was obtained by collagenase type II digestion (Sigma Aldrich, Milano, Italy) at 37 • C for 1 h in agitation.…”
Section: Hasc Isolation and Culturementioning
confidence: 99%
“…The interference of the higher concentrations with cell proliferation is probably due to both AuNPs and the ions released by dissolution. Previous studies have also reported that cells can return to their normal state if not compromised by mechanical damage such as massive internalization. Given that ROS is directly related to AuNPs cytotoxicity, the level of ROS was measured after 24 and 48 h incubation with 1.25–10 μg/mL of the three different functionalized AuNPs in A549 cells. ROS can dynamically influence the tumor microenvironment survival, proliferation, and metastasis by enhancing intracellular oxidative stress. , Consequently, a potent method of combating cancer may be realized by disrupting the equilibrium of intracellular ROS to cause their elevation .…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that after their uptake, cells pass NPs to their daughter cells, and if no more NPs are added into the cell culture, the concentration of ZnO NPs inside the cell becomes increasingly diluted [ 54 ]. Other studies have reported that, after their uptake, NPs are partially degraded by the acidic pH of lysosomes and then released by exocytosis [ 55 , 56 , 57 ]. This may explain not only the decrease in NPs in the cell culture, but also the cell’s ability to return to its near normal status.…”
Section: Discussionmentioning
confidence: 99%